Care Allowances for the Frail Elderly and Their Impact on Women Care-Givers - Jenson, Jane (OECD Publishing, 2000)
This report discusses the impact of care allowances on women care-givers. These programmes, involving some payment for care in informal care settings, have recently been introduced in several OECD Member countries. While their primary goal has been to help older persons in need of care, their consequences for the persons providing care also deserve to be analysed. The bulk of informal care is provided by women care-givers. In this respect, long-term care systems involve a partnership between formal care systems, the state, and the family, in order to provide a continuum of care. This also renders the analysis very complex. The main objective of the paper is to answer the question: what is the impact for women care-givers of various models of care allowances for the frail elderly? These care allowances have been primarily instituted to address the needs of older persons for care, as well as to offer some compensation for caring responsibilities. Apart from these initial goals ...
Keywords: Social Issues/Migration/Health